Enforcement of labor regulations and job flows: Evidence from Brazilian cities - Ana Abras; Rita K. Almeida; Pedro Carneiro; Carlos Henrique L. Corseuil (IZA Journal of Development and Migration, 2018)
The frequency of labor inspections in Brazil increased in the late 1990s. In the years that followed, between 2003 and 2007, formal employment expanded significantly in the country. This paper examines whether these city-level changes in labor inspections could be a significant factor contributing to the increase in the number of formal labor contracts at the city level. We exploit unique administrative data on formal employment on different indicators for job and worker flows-including job creation, destruction, reallocation, accessions, and separations-between 1996 and 2006, and on the intensity of labor inspections, both at the city level. The results show that increases in the enforcement of labor market regulations at the subnational level led to an increase in gross and net formal job creation rates and accession rates in a period when the Brazilian GDP and formal employment were growing and informality rates were declining. In contrast, increases in enforcement of regulations are not significantly correlated with changes in the rate of job destruction. This finding is robust to different specifications and is consistent with a model where formal jobs become more attractive to workers when enforcement of different types of labor regulations increases.
Keywords: J21; J63; E24; H80; C23; 330; Formal employment growth; Job flows; Enforcement labor market regulations; Panel data